2015
DOI: 10.1590/0103-6440201300198
|View full text |Cite
|
Sign up to set email alerts
|

Is the Masticatory Function Changed in Patients with Temporomandibular Disorder?

Abstract: Patients with temporomandibular disorders (TMD) often complain and have limitation in masticatory function, which can be affected by a complex interaction of factors. The aim of this study was analyze the masticatory function in patients with TMD using surface electromyography (EMG) and masticatory efficiency (ME). Twenty-seven patients with TMD and 25 considered control (n), aged between 18 and 60 years, paired by age and gender, were evaluated according to RDC/TMD. In both groups were performed: EMG with che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 22 publications
(30 reference statements)
1
40
0
7
Order By: Relevance
“…From the 17 selected studies, fifteen of them used RDC/TMD protocol for TMD diagnosis and the other two studies used the Helkimo Protocol . The studies which used RDC/TMD protocol presented a sample with only masticatory muscles disorders, a sample with mixed TMD, a sample with the 3 subtypes of TMD (TMJ disorders, masticatory muscles disorders or mixed), samples with TMJ disorders and mixed TMD, and samples with only mixed TMD . Regarding two articles that used Helkimo Protocol, one of them presented a sample with minor, moderate, and severe TMD, and the other presented a sample with moderate and severe TMD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 17 selected studies, fifteen of them used RDC/TMD protocol for TMD diagnosis and the other two studies used the Helkimo Protocol . The studies which used RDC/TMD protocol presented a sample with only masticatory muscles disorders, a sample with mixed TMD, a sample with the 3 subtypes of TMD (TMJ disorders, masticatory muscles disorders or mixed), samples with TMJ disorders and mixed TMD, and samples with only mixed TMD . Regarding two articles that used Helkimo Protocol, one of them presented a sample with minor, moderate, and severe TMD, and the other presented a sample with moderate and severe TMD.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding two articles that used Helkimo Protocol, one of them presented a sample with minor, moderate, and severe TMD, and the other presented a sample with moderate and severe TMD. Studies which used RDC/TMD were conducted in Brazil, Chile, Italy and United States, whilst studies which used Helkimo Protocol were conducted in Mexico and Spain . A summary of the studies descriptive characteristics can be found in Table and the sEMG characteristics are available in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fazem parte de um espectro de síndromes associadas ao estresse e são caracterizados por fatores ambientais e psicológicos 3 , incluindo fadiga, prejuízo das atividades do trabalho e escola, distúrbios do sono e do apetite/alimentação, ansiedade e depressão 4. A etiologia das disfunções da ATM é multifatorial 5 e os fatores que contribuem para o desenvolvimento das mesmas incluem má oclusão, fatores traumáticos, doenças sistêmicas, hábitos parafuncionais 6 , alterações posturais e stress e ansiedade 7 . Sabe-se que os sinais e sintomas mais observados em pacientes com DTM são limitações da amplitude de movimentos mandibulares, dor ou desconforto, ruído articular, dificuldade na mastigação e cefaleia (8)(9)(10)(11) . A DTM tem sido identificada como a primeira causa de dor não dental em região orofacial 4 .…”
Section: Introductionunclassified
“…7 For the assessment of TMD according to the applicability and researcher or clinician purposes, questionnaires, imaging tests such as x-rays, computed tomography, magnetic resonance imaging and clinical assessment has been used. 8 The research diagnostic criteria for TMD standardize the diagnosis and classification of clinical forms of TMD.…”
mentioning
confidence: 99%